A Comprehensive Analysis of Students’ Enrollment Trends in Tertiary Education - Trital, Noda Nath; Kharel, Suman; Acharya, Bisna (Curriculum Development Journal, 2023)
The present study aims to analyze the enrollment patterns of students in tertiary education in Nepal. This paper also presents a comparative analysis of Tribhuvan University (TU) and other Tertiary Education Institutions (TEIs) in terms of their production of both technical and non-technical graduates. The descriptive and analytical research design has been applied to analyze the data which was collected from secondary sources over the period of 10 years. The collected data has been thoroughly analyzed and expertly presented in a variety of graphics. The findings of the study reveal a consistent annual increase in the number of students pursuing higher education, with a notable upward trend among female students. Over the past decade, there has been a notable increase in the number of students obtaining No Objection Certificates (NOCs). Tribhuvan University (TU), a highly esteemed tertiary education institution in Nepal, plays a crucial role in providing over 76% of tertiary education in the country. The enrollment patterns in tertiary education reveal that a significant number of students have obtained NOCs from the Ministry of Education, Science and Technology (MOEST) to pursue higher education abroad upon completing their secondary education. The extensive research, socioeconomic, demographic, and institutional factors interact to affect higher education enrollment. The existing guidelines, policymakers, educational institutions, and other stakeholders can create inclusive, equitable, and flexible higher education systems that meet students’ diverse needs and advance social and economic progress.